2015
DOI: 10.2478/jomb-2014-0037
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Low Density Lipoprotein and High Sensitive C-Reactive Protein in Non-Diabetic, Pre-Diabetic and Diabetic Patients in the Acute Phase of the First Myocardial Infarction Treated by Primary Percutaneous Coronary Intervention / Oksidovani Lipoprotein Niske Gustine I Visokosenzitivni C-Reaktivni Protein Kod Nedijabetičara, Predijabetičara I Dijabetičara U Akutnoj Fazi Prvog Infarkta Miokarda Lečenog Primarnom Perkutanom Koronarnom Intervencijom

Abstract: SummaryBackgroundOxidized low density lipoprotein (ox-LDL) and high-sensitive C-reactive protein (hs-CRP) are elevated in diabetes mellitus (DM) and associated with accelerated atherosclerosis. Little is known about their dynamics in the acute phase of ST segment elevation myocardial infarction (STEMI), especially in relation to the presence of DM and pre-diabetes (pre-DM). This study aimed to analyze time-dependent changes in ox-LDL and hs-CRP regarding the presence of pre-DM and DM in STEMI patients treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It is believed that apoB levels and the apoB/apoA1 ratio may be useful predictors of cardiovascular events and that elevated levels of plasma apoB and/or apoB/apoA1 ratio may be the reason for the in creased hsCRP levels and the onset of inflammation in the vasculature (22). Data obtained in the Lu M. et al (23) study show that the subjects with higher BMI, waist/hips circumference ratio, SBP and DBP mean values and triglycerides and total cholesterol levels in the blood, have a higher risk of cardiovascular events (24, 25).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that apoB levels and the apoB/apoA1 ratio may be useful predictors of cardiovascular events and that elevated levels of plasma apoB and/or apoB/apoA1 ratio may be the reason for the in creased hsCRP levels and the onset of inflammation in the vasculature (22). Data obtained in the Lu M. et al (23) study show that the subjects with higher BMI, waist/hips circumference ratio, SBP and DBP mean values and triglycerides and total cholesterol levels in the blood, have a higher risk of cardiovascular events (24, 25).…”
Section: Discussionmentioning
confidence: 99%
“…Although LDL-C value is known as a strong risk factor for CVD, it is not always elevated in CVD patients. Numerous studies suggested that serum sdLDL value is thought to be a more atherogenic factor so that its measurement may be useful for evaluating CVD risk (15) . Furthermore, a number of studies reported that serum sdLDL is a primary factor for the development of atherogenic events (16) .…”
Section: Discussionmentioning
confidence: 99%
“…hs-CRP is one of the most well-established biomarkers of chronic inflammation. hs-CRP produced by tissue macrophages and vascular smooth muscle cells could appear in the atherosclerotic plaques (14). Jia and associates showed that coronary artery atherosclerotic patients have higher hs-CRP levels than non coronary artery atherosclerotic patients (15).…”
Section: Discussionmentioning
confidence: 99%